2011
DOI: 10.1093/treephys/tpr070
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-B-induced flavonoid accumulation in Betula pendula leaves is dependent upon nitrate reductase-mediated nitric oxide signaling

Abstract: Nitric oxide (NO) is an important signaling molecule involved in many physiological processes in plants. Nitric oxide generation and flavonoid accumulation are two early reactions of plants to ultraviolet-B (UV-B) irradiation. However, the source of UV-B-triggered NO generation and the role of NO in UV-B-induced flavonoid accumulation are not fully understood. In order to evaluate the origin of UV-B-triggered NO generation, we examined the responses of nitrate reductase (NR) activity and the expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…This suggested that under the UV-B radiation stress, NOS in Larix gmelinii seedlings leaves could promote the synthesis of NO. This result is in agreement with the results of Ming Zhang et al [38]. SNP treatments were applied under enhanced UV-B radiation.…”
Section: Discussionsupporting
confidence: 93%
“…This suggested that under the UV-B radiation stress, NOS in Larix gmelinii seedlings leaves could promote the synthesis of NO. This result is in agreement with the results of Ming Zhang et al [38]. SNP treatments were applied under enhanced UV-B radiation.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have focused on elicitors for the induction of plant secondary metabolite accumulation and the signal transduction pathway. Zhang et al (2011) demonstrated that NO induces the expression of the flavonoid biosynthetic NIA1 genes, and flavonoid synthesis. SA enhances the accumulation of secondary metabolites and expression of defense genes in Atractylodes lancea DC (Wang et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of NO by haemoglobin assay NO accumulation was assayed and calculated by following the conversion of oxyhemoglobin (HbO 2 ) to methemoglobin (MetHb) at 401 and 421 nm, using an extinction coefficient of 77 mm -1 cm -1 (A 401 HbO 2 , A 421 MetHb) (Zhang et al 2011). Oxyhemoglobin was prepared as detailed previously .…”
Section: Measurement Of Hypocrellin Contentmentioning
confidence: 99%
“…Zhang et al (2011) have proved that NO derived from NR plays a role in conferring UV-B stress tolerance. Direct association between NR activity, NO emission and nitrite (NO 2 − ) content was determined in silver birch (Betula pendula) under UV-B radiation.…”
Section: Uv-b Radiationmentioning
confidence: 99%
“…It was confirmed that NR activity and NO emission are required for flavonoid accumulation in silver birch, and NO scavenger cPTIO abolished NO. Although a role for an NOS-like source for NO during UV-B stress was suggested in maize and G. biloba (Hao et al 2009;Tossi et al 2009a), the effect of mammalian NOS inhibitors on UV-B-induced NO generation cannot be shown by Zhang et al (2011).…”
Section: Uv-b Radiationmentioning
confidence: 99%